2012
DOI: 10.1091/mbc.e11-06-0487
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 phosphorylation by cyclin A2/cyclin-dependent kinase 2 is required for zebrafish embryogenesis

Abstract: Although UHRF1 is essential for many epigenetic marks, the mechanism that regulates UHRF1 is not understood. This study shows that a key component of the cell cycle machinery—cyclin-dependent kinase 2/cyclin A2—phosphorylates UHRF1 and that this phosphorylation is essential for early zebrafish development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 70 publications
(139 reference statements)
4
60
1
Order By: Relevance
“…To determine whether this acute cell cycle block in uhrf1 mutants contributed to the uhrf1 mutant phenotype at 120 hpf, we used a heat-shock inducible transgene [Tg(hsp70l:UHRF1-GFP) (Chu et al, 2012)] to replace UHRF1 expression transiently in the embryo at 24, 32, 54 and 72 hpf, and then assessed larvae at 120 hpf for overall (Fig. 4C) and hepatic (Fig.…”
Section: Cell Cycle Arrest Results In Apoptosismentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether this acute cell cycle block in uhrf1 mutants contributed to the uhrf1 mutant phenotype at 120 hpf, we used a heat-shock inducible transgene [Tg(hsp70l:UHRF1-GFP) (Chu et al, 2012)] to replace UHRF1 expression transiently in the embryo at 24, 32, 54 and 72 hpf, and then assessed larvae at 120 hpf for overall (Fig. 4C) and hepatic (Fig.…”
Section: Cell Cycle Arrest Results In Apoptosismentioning
confidence: 99%
“…We next asked whether Uhrf1 was required in a cell-autonomous fashion during hepatic outgrowth by crossing uhrf1 mutants to a transgenic line expressing low levels of UHRF1-GFP exclusively in hepatocytes [Tg(fabp10:UHRF1-GFP) LOW , hereafter referred to as UHRF1-GFP Low] (Chu et al, 2012;Mudbhary et al, 2014). The non-hepatic phenotypes were not altered in uhrf1 mutants expressing UHRF1-GFP Low in hepatocytes (Fig.…”
Section: Cell Cycle Arrest Results In Apoptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, genome-wide association studies of Crohn's disease and ulcerative colitis patients have identified SNPs near UHRF1, DNMT1, and DNMT3a (37,38), suggesting that alterations in these genes may lead to IBD. Although alternative roles for UHRF1 including cell cycle regulation and histone ubiquitylation have been identified (39)(40)(41), up-regulation of tnfa in the intestine of both uhrf1 pd1092 and dnmt1 pd1093 mutants strongly suggests that it is the loss of DNA methylation at CpG dinucleotides at the tnfa promoter that leads to elevated tnfa expression.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin-like with plant homeodomain (PHD) and RING finger domain 1 (UHRF1) is a multi-domain protein, which was initially identified as a nuclear protein associated with cell proliferation (4). As a human inverted CCAAT box-binding protein, UHRF1 is involved in regulating the expression of topoisomerase IIα in proliferating cells (5).…”
Section: Introductionmentioning
confidence: 99%